Keseimbangan Peran Gender dalam Al-Qur’an (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2022)
Gender is one of the contemporary social discourses that never ends. Not infrequently this issue is considered a sensitive theme, especially in the Islamic world. The echo of demands for gender equality that is often heard in the West, is considered inappropriate in Islam. Because Islam has perfectly organized and organized this life. This includes equality between men and women. However, this does not mean that the equation means equality between the two in all aspects. Islam has determined men and women according to their respective portions, both in rights and obligations. What is important to note is that both of them absolutely have mutual tendencies, according to their respective abilities, expertise and portions. This is what is called a balance of roles, to complement each other and partner/work together in navigating life, such as in terms of taking care of and caring for the earth and structurally functional in a household. Men and women have their respective portions to complement each other and carry out their roles. For this reason, the equality referred to by Islam is equality that indicates harmony and balance between men and women, which is built on the Shari'ah, relies on the principle of partnership, not to outperform or precede each other.
Keywords: Gender; Al-Qur'an; Role Balance; Equality